The Influence Of Content Marketing, Brand Image And E-Service Quality On Consumer Satisfaction At Kopi Kenangan In Jalan Setia Medan - Muhammad Tegar Dwinata; Annisa Sanny; Slamet Widodo (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of Content Marketing, Brand Image, and E-Service Quality on Consumer Satisfaction at Kopi Kenangan on Jalan Setia Medan. This study applies a quantitative approach through a survey method to 96 respondents who are active consumers. The data analysis technique used is multiple linear regression through SPSS software version 22. These findings show that partially Content Marketing has a negative and significant effect on Consumer Satisfaction (B = -0.147; t = -5.304; Sig. = 0.000). Brand Image has a positive and significant impact on Consumer Satisfaction (B = 0.083; t = 2.816; Sig. = 0.006). Meanwhile, E-Service Quality has a positive and significant impact on Consumer Satisfaction (B = 0.629; t = 13.094; Sig. = 0.000). The results of simultaneous testing show that Content Marketing, Brand Image, and E-Service Quality simultaneously have a significant effect on Consumer Satisfaction (F = 63.980; Sig. = 0.000). The Adjusted R² value of 0.665 indicates that 66.5% of the variation in Consumer Satisfaction can be explained by the research model, and 33.5% is influenced by other factors outside the research. The findings of this study indicate that E-Service Quality is a very dominant variable in increasing the level of Consumer Satisfaction. Therefore, companies need to increase the level of digital service quality, accompanied by an evaluation of content marketing strategies and strengthening brand image to support the continuous improvement of consumer satisfaction.